ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Sitti Nur Annisa Rumasukun; Nurwidianto Nurwidianto; Agnes Soukotta (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2019)
This study aims to analyze whether there is an effect of profitability , liquidity and sales growth on the capital structure of manufacturing companies in the period 2014-2018. The sampling technique used was purposive sampling with a sample of out of 149 manufacturing companies. The analysis technique used is multiple linear regression analysis and hypothesis testing using T-statistics to test the partial stress coefficient and F-statistics to test the effect together or simultaneously. The results of the research partially show that profitability and liquidity have a significant negative effect on DER while sales growth has a significant positive effect on DER. The results of the study simultaneously show profitability, liquidity and sales growth jointly influence the DER.